Caracterización del deslizamiento presente en el barrio Chinguilanchi y Amable María sector noreste de la ciudad de Loja, con miras al desarrollo de un plan de previsión y prevención de movimientos de masa. - Chávez Ordóñez, David Eugenio (2011)
The present investigation, focuses the use of the Systems of Geographical Information (SIG) to the determination of risk areas to mass movements in the Northwest sector of the city Loja specific in the barrios Chingilanchi y Amable María. With this perspective it has been carried out the evaluation of the susceptibility based on a theoretical system, which consists on evaluating the biggest number in conditioning factors of the land quantitatively which influence directly in the appearance of mass Movements. He/she has taken as starting point topographical digital information of the study sector with scale to detail (1:1 500); based on this information and with the help of field works it has been obtained thematic maps of: geology, slopes, floor type, precipitations, vegetation, and susceptibility of slips. Each variable that constitutes each one of these thematic maps, has been valued based on the capacity that has each one of them to be prone to the mass movements. With the help of the Systems of Geographical Information, they were in digital form each one of the variables analyzed to superimpose the thematic maps and to obtain the map where the areas of risk are shown to mass movements. This obtained information, as much in digital form as in similar form will serve as base and starting point for the implementation of a correct Territorial Classification with an eye toward a Sustainable Development of the urban sector Chinguilanchi and Amable María of Norwest of the city Loja, facilitating this way so much the taking of decisions and the appropriate handling of the resources human, as environmental and economic.